Motility and recovery of alpaca (Vicugna pacos) spermatozoa after centrifugation in a density gradient solution - Gómez Quispe, O. E. (2019)
Background: One of the factors limiting successful processing of alpaca (Vicugna pacos) semen is the viscosity of seminal plasma. The viscous nature of the collected ejaculate has hindered sperm cryopreservation as well as artificial insemination (AI) under field conditions. Aims: The objective of this investigation was to evaluate recovery, motility, and plasma membrane integrity of alpaca spermatozoa after centrifugation in one of two different solutions at one of three different combinations of speed and time. Methods: A total of 24 ejaculates was recovered from seven reproductively sound Huacaya males using a modified artificial vagina (AV) after training the animals for semen collection. A 2 × 3 factorial treatment arrangement was utilized for this study. Ejaculates were divided into fractions for centrifugation in one of two solutions (Tris extender or PureSperm®80 density gradient solution) at one of three combinations of speed and time (492 × g for 15 min, 1968 × g for 10 min, or 4448 × g for 7 min). The experiment was replicated eight times. Results: Analysis revealed that centrifugation at 4448 × g for 7 min in PureSperm®80 provided a high recovery rate of spermatozoa with the highest sperm motility and functional integrity of plasma membrane post-centrifugation. Conclusion: Results suggest that adoption of this procedure (centrifugation at 4448 × g for 7 min in PureSperm®80) in the initial processing of alpaca ejaculates may enhance subsequent ability to use semen for AI and other assisted reproductive biotechnologies in this species